Framing Of Oil Pollution News: A Study Of Three Selected Newspapers In The Niger-Delta, Nigeria From 2008-2018 - Ebere, Odoemelam Chika (2021)
This study wittingly examines the framing of oil pollution news among three selected newspapers in Niger-Delta, Nigeria, from 2008-2018. The study explored contents in three Nigerian newspapers, The Daily Sun, The Guardian, and The Punch, in their news coverage on oil pollution in the Niger-Delta region.